Characteristics of Magic Realism in F.Kafka`s Short Stories and Novels (Eurasian Journal of Philology Science and Education, 2018)
In the second half of the 20th century, Latin American literature turned «magical realism» into the leading method of fiction. The main features of magical realism are not the explanation of fantastic elements, characters accept and do not challenge the logic of magic elements, symbols and images are often used, distortion of the flow of time, etc. Kafka’s prose, combining surreal and absurd elements, created the most illustrative example of magical realism. Simplicity, which took the form of mystical horror, the reception of strangeness, reached a high degree and all this is a special sign of Kafka’s work. His absurd hero, living in the world, tragic, touching zeal, wants to open his way in the world of people, but he meets his death in a poor and broken state. In the works of Kafka, the transformation of existing reality into a deeper reality, and the fact that this reality is accepted without causing any surprise is connected precisely with the aesthetics of magical realism.